Abdominal Stetching Excercise On Decreasing Dysmenorrhea in Girl Adolescent - Nataria, Desti; Putri, Vicky Elvira (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Dysmenorrhea is a problem associated with menstruation, the short pain before or during menstruation. One of non-pharmacological treatment for dysmenorrhea is Abdominal Stretching Exercise. The abdominal stretching exercise which is the exercise for increasing the power of abdominal muscles, increase oxygenation, fix elasticity, or flexibility of body tissues, reduce muscle cramp, then increase amount and size vessels blood, with channeling blood to all body including reproductive organs so can to reduce dysmenorrhea. The aims of this research were to know the Effect of Abdominal Stretching Exercise on Decreasing the Level of Dysmenorrhea for the adolescent girl. This quasi-experimental research is implemented with One Group Pretest-Posttest Design in MAN 1 Bukittinggi the sample of this study were 14 adolescent who experienced dysmenorrhea, the sample in this research and taken in purposive sampling. Data were collected withÂ the Faces Pain Rating Scale. Data were analyzed with Paired T-Test Sample. There is a difference between pain intensity before and after abdominal stretching exercises. There was an effect of Abdominal Stretching Exercise on Decreasing the Level of Dysmenorrhea for adolescents. Based on the result of the research above is expected for respondent after knowing abdominal stretching exercise could add insight and could to apply when the feel dysmenorrhea